Risk Perception of HIV and Perceived Barriers to Compliance with Standard Precautions among Healthcare Workers in Lower Manya District - Akagbo, S.E. (University of Ghana, 2013)
Human Immunodeficiency Virus (HIV) is a devastating health condition that affects every sphere of society including workplaces. A number of occupational exposures to patients‟ blood and body fluids occur each year in health-care settings putting healthcare workers (HCWs) at a high risk of several blood-borne infections including human immunodeficiency virus (HIV), hepatitis B (HBV), and hepatitis C (HBC). This study investigated the health care provider‟s risk perception of HIV, knowledge on standard precautions (SPs), barriers and rate of compliance with standard precautions and also work related injuries faced by the HCWs.A Self-administered semi-structured questionnaire was use to elicit responses from one hundred healthcare workers comprising of laboratory technicians, midwives, nurses and ward aides. Majority of the participants regarded HIV as a public health issue and most of them perceived that they were at risk of contracting HIV on the job. Data revealed good compliance with standard precautions (SPs) among quite a number of HCWs. However, most of the HCWs were of the view that complying with standard precautions (SP) during emergency situations sometimes put the patients at risk and therefore they were likely not to adhere. Knowledge of the basic concept of the standard precautions was inadequate among the health care workers and most of the HCWs sometimes experience chemical splashes in the cause of their duty. Despite the risk of non-compliance and benefits of compliance with universal precautions, HCWs still often fail to strictly adhere to universal precautions. Therefore, interventions need to address individual provider‟s attitudes and emphasize that universal precautions are standard practice and not just for a special group of patients but for all patients. Key words: Health care workers, Risk perception, HIV, Barriers to Compliance, standard precautions.
Thesis (MSc)-University of Ghana, 2013